Possessive agreement in Insular Celtic - Matasović, Ranko (Studia Celtica Posnaniensia, 2024)
Possessive agreement is a pattern of NP-internal agreement in which certain features of the possessor (usually person, number and/or gender) are marked twice within the NP: firstly, on the possessive marker itself (e. g. a possessive pronoun) and secondly, on another morpheme, which obligatorily agrees in those features with the possessive marker (Corbett 2006: 47). This type of agreement is not common in Indo-European languages, but it is in Uralic and several other language families in Eurasia (Koptjevskaja-Tamm 2003). However, Goidelic and Brittonic have constructions falling under the above definition in which the pronominal possessor can be marked by two pronominal elements which have to agree in person, number and (in the third person singular) gender. In both languages, the first pronominal element is the proclitic possessive pronoun. In Old Irish, the second pronominal element referring to the possessor is traditionally called the “emphasizing particle, or nota augens” (Thurneysen 1946: 252–3, Griffith 2008), and it distinguishes the same categories as the possessive pronouns. The second pronominal element in Middle Welsh is identical to the stressed simple personal pronouns. This paper investigates the phenomenon of possessive agreement in Insular Celtic by examining the frequencies of possessive constructions with agreement in selected Old Irish and Middle Welsh texts, and seeking to establish the pragmatic functions of these constructions. Additionally, by looking at the earliest attestations of constructions with possessive agreement it will be shown that it is unlikely that they should be reconstructed in Proto-Insular Celtic (or even Proto-Celtic). Rather, it is argued that possessive agreement in Insular Celtic developed as an areal phenomenon which arose in situations of intensive language contact that occurred in Britain and Ireland during the Early Middle Ages (Matasović 2007).